Somatic Embryogenesis of Myrciaria dubia (Kunth.) McVaugh - Edvan Alves Chagas; Jonathan H. Crane; Pollyana Cardoso Chagas; Wagner Vendrame; Barbara Nogueira Souza Costa; Aurélio Rubens Neto; Maria Conceição Rocha Araújo; Caroline de Araújo Machado; Elias Ariel Moura (HortScience, 2023)
Myrciaria dubia (caçari or camu-camu) is a species with great relevance because of its high levels of bioactive compounds and antioxidant activity. The species is propagated mainly by seed, which leads to high genetic diversity. Producing plants that maintain their characteristics on a large scale at a low cost is a challenge for fruit species, especially in the Myrtaceae family. Therefore, this study aimed at assessing the effects of different plant growth regulators at various concentrations for the induction of somatic embryogenesis from caçari nodal segments and leaf disk explants. Two independent experiments were performed using nodal segments and leaf disks from plants grown in the greenhouse. In the first experiment, the combined effect of auxin and cytokinin at different concentrations was evaluated: 2,4-dichlorophenoxyacetic acid at 0, 1, 2, and 4 mg⋅L–1; and benzylaminopurine at 0, 0.25, 0.5, and 1 mg⋅L–1). In the second experiment, the application of different plant growth regulators (benzylaminopurine, kinetin, thidiazuron, and isopentenyl adenine) and their concentrations (0, 2, 4, and 6 mg⋅L–1) were evaluated. In both experiments, the basic culture medium was woody plant medium. Callus formation via nodal segments and leaf disks occurred in the first 30 d from cultivation and proved to be responsive to induction by 2,4-dichlorophenoxyacetic acid and benzylaminopurine. Auxin proved to be essential for somatic embryogenesis induction in nodal segments using 1 and 4 mg⋅L–1 of 2,4-dichlorophenoxyacetic acid alone. The results of this experiment will help advancing protocols for regeneration of somatic embryos and elucidating the physiological, molecular, and genetic mechanisms involved in the process of somatic embryogenesis for M. dubia. The development of an efficient protocol for in vitro clonal propagation of this species also lays the groundwork for further optimization of the system for genetic transformation.